P052 EARLY OPERATIVE OUTCOMES OF ENHANCED-VIEW TOTALLY EXTRA PERITONEAL REPAIR(ETEP) FOR VENTRAL HERNIAS. (25th November 2021) - Imamura, Kiyotaka; Takada, Minoru; Ambo, Yoshiyasu
Abstract: Aim: Early operative outcomes of enhanced-view totally extraperitoneal repair (eTEP) for ventral hernias Material and Methods: We have retrospectively analysed the date of 41 patients who underwent an eTEP procedure on between November 2018 and April 2021 by a single surgeon and monitored until May 2021. Results: During the study period, 29 endoscopic transversus abdominis muscle release and 12 endoscopic Rives-Stoppa techniques were performed to repair incisional (30), umbilical (6), epigastric (3), and spigelian, and parastomal hernias occurred in 1 patient each. The mean age was 68.0 years, mean BMI was 26.4 kg/m2. The hernial orifice centers were as follows: M2 in 7, M3 in 23, M4 in 5, L2 in 4, L4 in 1, and M2 and L2 (2 orifices) in 1 patient. Nine cases of large incisional hernia (width ≥10cm) were included. An average mesh area of 624cm 2 was used for an average defect area of 57cm 2 . Mean operative time, blood loss, and length of hospital stay were 278 min, 5 ml, 6 days, respectively. Only one case was converted to an open operation due to presence of severe adhesions. Postoperative complication consisted of hematoma (n = 1) and a small bowel obstruction due to a tear of the posterior sheath (n = 1). There was no hernia recurrence at mean follow-up of 448 days. No patient reported significant pain at the surgical site at the first postoperative follow up. Conclusions: Judging from our short-term results, eTEP approach for ventral hernias can be an attractive option for selected cases.